Abundance : the future is better than you think - Diamandis, Peter H. (Free Press, 2012)
The authors document how four forces--exponential technologies, the DIY innovator, the Technophilanthropist, and the Rising Billion--are conspiring to solve our biggest problems. "Abundance" establishes hard targets for change and lays out a strategic roadmap for governments, industry and entrepreneurs, giving us plenty of reason for optimism.- Resumé vxydavatel
Free Press paperback edition September 2014.
Keywords: inovace -- prognózy; technologie -- sociální aspekty; ekonomické prognózování; sociální prognózování; innovations -- forecasting; technology -- social aspects; economic forecasting; social forecasting; elektronické knihy; populárně-naučné publikace; electronic books; popular works